Thermal design of a finned tubes economizer - Pérez Sánchez, Amaury; Acosta Pérez, Noemí; Valero Almanza, Greisy I.; Ranero González, Elizabeth; Pérez Sánchez, Eddy J. (Nexo Revista Científica, 2021)
An economizer is a finned tube heat exchanger that makes it possible to recover part of the sensible heat of the combustion products emitted by a boiler, transferring it to the feed water and thus increasing thermal efficiency. In the present work, the design of an economizer of tubes with helical fins was carried out to accomplish the preheating of a feed water that is at a temperature of 25 ºC, by using combustion gases at 240 ºC as heat transfer agent which are emitted by burning Fuel-Oil in a fire tube boiler. The water will heat up to 73.27 °C, and both the global heat transfer coefficient and the heat transfer surface area had values ​​of 19.947 W/m2.K and 95.146 m2, respectively. The economizer designed will have a length of the finned tubes of 65.482 m, a total number of tubes of 131, a number of transverse rows of tubes of 16, a depth of the gas conduit of 0.765 m, an actual number of tubes of 144 and an actual length of the finned tubes equal to 72.